Extremely tortuous coronary arteries – When optical coherence tomography and fractional flow reserve did not help us much - Miloradovic, Vladimir; Nikolic, Dusan; Sreckovic, Miodrag; Djokic Nikolic, Ivana (Vojnosanitetski pregled, 2020)
Introduction. Extreme coronary tortuosity may lead to flow alteration resulting in a reduction in coronary pressure distal to the tortuous segment, subsequently leading to ischemia. Therefore the detection of a true cause of ischemia, i.e. whether a fixed stenosis or tortuosity by itself is responsible for its creation, with non-invasive and invasive methods is a real challenge. Case report. We presented a case of a patient with a history of stable angina [Canadian Cardiovascular Society (CCS class II)], an abnormal stress test and coronary tortuosity without hemodynamically significant stenosis. Due to suspected linear lesion between the two bends in proximal segment of Right coronary artery (RCA) we performed optical coherence tomography (OCT), minimum lumen area (MLA)-13.19 mm2) and fractional flow reserve (FFR) RCA (0.94). We opted for conservative treatment for stable angina. Conclusion. When tortuosities are associated with atherosclerosis in coronary artery for determination of true cause of ischemia invasive methods can be used, such as OCT and FFR.
Keywords: coronary vessels; angina pectoris; blood flow velocity; coronary angiography; tomography, optical coherence